2008
DOI: 10.1038/nm1721
|View full text |Cite
|
Sign up to set email alerts
|

A20 is an antigen presentation attenuator, and its inhibition overcomes regulatory T cell–mediated suppression

Abstract: Regulatory T cells (T reg ) suppress autoreactive immune responses and limit the efficacy of tumor vaccines; however, it remains a challenge to selectively eliminate or inhibit T reg . In this study, A20, a negative regulator of the TLR and TNFR signaling pathways, was found to play a critical role in controlling the maturation, cytokine production, and immunostimulatory potency of dendritic cells (DC). A20-silenced DCs with the spontaneous and enhanced expression of costimulatory molecules and proinflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
162
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(168 citation statements)
references
References 44 publications
5
162
1
Order By: Relevance
“…Recently, Song et al (40) silenced A20 in mouse DCs and demonstrated that this down-regulation results in up-regulation of different cell surface Ags associated with DC activation and the increased production of IL-6, IL-12p40 and TNF-␣ even in the absence of an activation stimulus. This is in contrast with our observations and our view on the role of A20, as a brake on TLR activation, in DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Song et al (40) silenced A20 in mouse DCs and demonstrated that this down-regulation results in up-regulation of different cell surface Ags associated with DC activation and the increased production of IL-6, IL-12p40 and TNF-␣ even in the absence of an activation stimulus. This is in contrast with our observations and our view on the role of A20, as a brake on TLR activation, in DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Gene silencing of SOCS1 or A20 in DC was observed at a siRNA dose of 80 nM, whereas the efficiency of gene silencing was only modest (40-70%) [15,16]. On the other hand, a viral vector achieved more than 80% gene silencing [3,4]. Based on these findings, it is clear that a breakthrough delivery system is needed for the efficient introduction of siRNA to DCs.…”
Section: Introductionmentioning
confidence: 94%
“…RNAi technology can selectively control the expression of target molecules, resulting in the strict control of DC functions. Gene silencing of negative-feedback factors in DCs, such as the suppressor of cytokine signaling 1 (SOCS1) and A20, would be expected to greatly stimulate cytokine production and antitumor activity [3,4]. In addition to improving the strength of immunity mediated by DCs, gene silencing of the transforming growth factor β (TGF-β) receptor in DCs can result in the prevention of tumor-associated immunosuppression, because DC functions are also suppressed by TGF-β in a tumor microenvironment [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A20 knockdown in dendritic cells results in enhanced expression of specific co-stimulatory signals as well as pro-inflammatory cytokines, causing a shift in the subset of activated T cells. Both cytotoxic T cells and T helper cells were hyperactivated, whereas regulatory T cells were markedly suppressed, with beneficial anti-tumor effects as a result (10).…”
Section: Inhibitory Effect Of A20 On Pro-inflammatory Gene Expressionmentioning
confidence: 99%